The Attitudes Of VAT Taxpayers Toward The Use Of E- Tax Systems And Their Impact On Tax Compliance: A Field Study Of Tabuk Region - Ershaid, Dr. Oglah Nawash (The journal of contemporary issues in business and government, 2021)
This study aims to identify the attitudes of value-added tax taxpayers towards e- tax systems and their impact on tax compliance. As such, this study answers questions about the Attitude of VAT payers towards e-tax systems, and whether it has an impact on the adoption of these systems as well as tax compliance. This paper has been composed based on two theories: Theory of Reasoned Action and Technology Acceptance Model (TAM) with the integration of the following variables: adoption of tax systems, tax compliance, and computer skills. This study revealed that a positive attitude has been shown as well as an adoption of e-applications by value-added taxpayers. In addition, this study indicated that there is compliance with this value-added tax. Furthermore, findings also showed that there is statistical significance of technical computer skills on adopting e- applications, taxpayers’ attitudes, and their adoption of e-applications in compliance with value-added tax. Finally, findings have shown that there is an effect of taxpayers’ adoption of e-applications as a mediating variable on the relationship between the attitudes of taxpayers towards e-applications and tax compliance.